A survey of strategies of implementing national orientation agency’s value programme in secondary schools in Osun State, Nigeria (2023)
This study examines the various strategies of implementing National Orientation Agency (NOA)'s moral value programme in secondary schools in Osun State. The study also examines the variation in the use of these strategies to determine their effectiveness on the implementation of the programme. Descriptive survey research design was adopted for the study which was guided by two research questions. The population for the study comprises of all NOA staff and secondary schools teachers in Osun State; while purposive sampling technique was used to select one hundred and twenty participants for the study. The instrument for the data collection was a constructed ten items structured questionnaire related to the strategies and the frequency use of these strategies were designed for the study. The instrument was subjected to face and content validity by Social Studies experts for scrutiny and review and validated two weeks before administration and its reliability was determined through Cronbach Alpha which yielded a co-efficient of 0.89. The data collected were analysed using descriptive statistics of frequency counts, percentage scores, mean and ranking order. The study revealed among others that most of the frequently used strategies were not appropriate for implementing the programme while appropriate strategies were seldomly used or not used at all. The study therefore recommended that NOA's staff should frequently use the appropriate strategies for implementing their programme so as to inculcate moral values into secondary schools students in Osun State.